Building an Environmentally Friendly Work Culture in Government Agencies Offices - Sugiarto, Agus (Universitas Pamulang, 2023)
Building an environmentally friendly work culture is a form of contribution to environmental conservation through employee activities in the workplace. This study aims to explore how to build an environmentally friendly work culture in government offices. This research is an exploratory qualitative research. The research informants consisted of six government employees or state civil servants who served in three government agency offices in three districts/cities in Central Java. The results of the exploration in this study there are five things that are done in building an environmentally friendly work culture at the government agency office. First, formulate and implement policy instruments on environmentally friendly behavior in government agencies. Second, strengthen the commitment and example of the leadership in being environmentally friendly. Third, implementing various environmentally friendly programs and actions in the office, in the context of empowering and involving state civil servants in the office. Fourth, use environmentally friendly office technology, and fifth, conduct socialization and training (education) on environmentally friendly work culture to state civil servants.